IMPLEMENTASI DIGITAL LIBRARY BATIK IKONIK PADA PEMBELAJARAN BATIK DI SEKOLAH MENENGAH KEJURUAN - Indah Nurjanah, - (2020)
This research departs from the problem of using technology media. The purpose of this study was to determine the usability aspect with five variables of perceived usefulness, perceived ease of use, perceived enjoyment, attitude towards / behavioral intention, and education on the iconic batik library digital media. This research method uses the TAM (Technology Accepted Model) approach. The sample of this research was all students of class XI textiles and productive teachers of SMK Negeri 14 Bandung as many as 67 people. The research instrument used questionnaire sheets that were distributed via google forms. The results obtained in this study were the iconic batik digital library media very helpful for students to get information about West Java batik, the batik digital library application is easy and can be used because it is easy to operate, students can develop batik motifs with the batik digital library source as a reference and help. students to study anywhere and anytime. Recommendations that can be conveyed through further research can add a user interface design variable so that the appearance can be seen by students and can add an observation instrument to test the variable attitude towards use/behavior to use (attitude towards / behavioral intention).